Metode Response Based Unit Segmentation Partial Least Square pada Model Partial Least Square Path Modeling - Utriweni Mukhaiyar; Karina Ayudhia Sasmito; Muh. Qodri Alfairus (Universitas Negeri Gorontalo, 2023)
Education is an important factor that can affect the development of a country and is a basic human need. To ensure the continuous progress of education, it is necessary to pay attention to the results and achievements of education in Indonesia. In this research model, Partial Least Square Path Modeling (PLS PM) is used to explain the relationship between education outcomes and achievements and the quality dimensions of provincial education in Indonesia. However, because there is heterogeneity in the population unit, the Response Based Unit Segmentation Partial Least Square (REBUS PLS) algorithm is used to overcome the alleged heterogeneity. The results showed that there were 20 influential indicators in the structural model, with the influential paths being student activities to participation, educational facilities and infrastructure to educational outcomes and achievements, student activities to educational outcomes and achievements, and participation to educational outcomes and achievements. REBUS PLS successfully detects heterogeneity and produces two segments, with the value of R2 on the local model greater than the value of R2 on the global model and the GoF value in the GoF large category.